2017
DOI: 10.1093/aobpla/plx060
|View full text |Cite
|
Sign up to set email alerts
|

Neutral molecular markers support common origin of aluminium tolerance in three congeneric grass species growing in acidic soils

Abstract: Aluminium (Al) toxicity is the main abiotic stress limiting plant productivity in acidic soils that are widely distributed among arable lands. Plant species differ in the level of Al resistance showing intraspecific and interspecific variation in many crop species. However, the origin of Al tolerance is not well known. Our most important result is that all Al-tolerant B. hybridum allotetraploid accessions from the western areas of the Iberian Peninsula (areas with acidic soils) have a common origin. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…These new markers could be used as a molecular tool to discriminate each species from the rest after testing these markers with more accessions from each species. A similar pattern had been described earlier to discriminate Brachypodium distachyon and Brachypodium hybridum species from each other (Contreras et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…These new markers could be used as a molecular tool to discriminate each species from the rest after testing these markers with more accessions from each species. A similar pattern had been described earlier to discriminate Brachypodium distachyon and Brachypodium hybridum species from each other (Contreras et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…It must be noted that these markers are yet to be tested on different populations of the same accession from a wide geographic range, or on other species in the Brachypodium genus. The expectation is that such analyses would yield multiple alleles, as has been shown by other studies [48,50,54]. The in silico sequence analyses showed that some of the regions selected for marker development were distant from areas that could reasonably be considered to be the promoter region for the designated gene (within 2 Kb upstream of the translation start site), and may in fact have been part of the structure of genes in a different orientation (Figure S1).…”
Section: Discussionmentioning
confidence: 83%
“…Since the inception of B. distachyon as a model system, many tools including markers have been developed to aid in research and discovery. Markers are available for the discrimination of different species in the genus Brachypodium , and within multiple populations of the same species [44,48,49,50,54]. In many cases, the length polymorphisms require the use of high percentage agarose gels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations